Different effect of green tea consumption on salivary antioxidant status in light versus heavy smokers - Azimi, Somayeh; Mansouri, Zahra; Bakhtiari, Sedigheh; Namdari, Mahshid; Afraz, Elham Sadat (Journal of Dental School, 2018)
Objectives Oxidative stress consequent to cigarette smoking may alter the salivary antioxidant defense system and lead to oral cancer. Green tea, with antioxidant properties, interacts with saliva upon entering the mouth. This experimental study explored the preventive effect of green tea on cigarette smoke-induced oxidative damage over 3 weeks. Methods In this clinical trial study sixty volunteer healthy male smokers (light and heavy) and non-smokers were selected according to the inclusion criteria. Participants of each three groups were instructed to drink 4g of green tea (prepared with 300 ml hot water) daily, for three weeks. Total antioxidant capacity of saliva was measured at baseline, after 7 days, and after 21 days in each group. Repeated measure ANOVA with Bonferroni adjustment was performed for statistical analysis. Results Non-smokers had a higher amount of salivary total antioxidant capacity at baseline (p<0.001). After 7days of green tea consumption total antioxidant capacity of non-smokers and light smokers showed no statistical difference (p=0.075), this trend continued until 21 days. In the heavy smokers total antioxidant capacity was still different from the other two groups (p<0.001). However, the maximum positive alteration of salivary total antioxidant capacity from day zero to day 21 occurred in the heavy smoker group (p< 0.001). Conclusion Although findings support the role of green tea drinking in reducing oxidative damage in saliva of both groups of smokers, heavy smokers showed the most significant change in total antioxidant capacity levels over three weeks.